O ADMINISTRATIVO E O PEDAGÓGICO NA GESTÃO ESCOLAR - Formiga, Maria das Graças Freire (2007)
This study is about the relation between the administrative and the pedagogic in the administration of the school, centered in the principal figure. It has as its main target to contribute with the reflection about this relation, using theoretic perspectives considered relevant and its discussions with professionals of the practice. The tasks which were dedicated to this theme relate that the school administration in Brazil is marked for distant and fragmented practices between the administrative and pedagogic dimensions, a dilemma that has the principal as a central character. They also show that this relation is a subject which needs reflections, debates and complementary analyzes. The research was developed through two main movements. The first involved a theoretic- bibliographic revision that ended into a selection of three theoretic perspectives which seemed to us, more relevant to the theme : i) the functional conflict (Saes & Alves), ii) from the inter-connection for the school administration (Medeiros) and iii) from the multi-referential vision (Barbosa). The second movement involved the search for inter-locution of these theoretic perspectives with the experience of two principals and two supervisors of education which work in the Secretaria de Educação do Estado de São Paulo. The results confirm the pertinence of the three theoretic contributions to the analyze and the relation between the administrative and the pedagogic in the school and its administration, although there has been some difficulties by the professionals of the practice in order to learn the pedagogic in the conception of the selected authors. It has been evidenced the pertinence of the conception and the understanding of the administrative and pedagogic dimensions under the perspective of relation .(AU)